THE SOCIAL AND PSYCHOLOGICAL CHARACTERISTICS OF AN EDUCATION MANAGER IN A HIGHER MILITARY EDUCATIONAL INSTITUTION - Abdullajonova, Dilnoza (Журнал Педагогики и психологии в современном образовании, 2025)
the article is about the main directions of accounting socio-psychological characteristics of the manager of education in the process of optimizing management activities. The identifying these directions will help for more efficient activity of manager.